2023
DOI: 10.1039/d2ra06919a
|View full text |Cite
|
Sign up to set email alerts
|

A novel hyperbranched polyethyleneimine–graphene composite as shale inhibitor for drilling fluid

Abstract: Structure of a hyperbranched polymer and graphene composite used as a shale inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Zhao et al synthesized hyperbranched polyethyleneimine/graphene composite (HPEI-G) as a shale inhibitor. 1 As shown in Fig. 3, HPEI-G has a better effect of inhibiting hydration at lower concentrations.…”
Section: Shale Inhibitor and Shale Plugging Agentmentioning
confidence: 84%
See 1 more Smart Citation
“…Zhao et al synthesized hyperbranched polyethyleneimine/graphene composite (HPEI-G) as a shale inhibitor. 1 As shown in Fig. 3, HPEI-G has a better effect of inhibiting hydration at lower concentrations.…”
Section: Shale Inhibitor and Shale Plugging Agentmentioning
confidence: 84%
“…The nanoscale size and flexible film structure of graphene-based materials allow them to plug nanopores and prevent water intrusion into clay minerals during the drilling process. 1 Their two-dimensional structure, which slides easily between layers, allows they to be used as a drilling fluid lubricant. 2 Their adsorption properties allow they to improve filtration performance in oily wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 To overcome these limitations, nanoparticles such as silica and graphene oxide (GO) were grafted with PEI to improve their properties. 15–17…”
Section: Introductionmentioning
confidence: 99%
“…However, this study is limited to a single concentration and a lower aging temperature of 65 °C. A recent study by Zhao et al 17 explored different PEI-GO and montmorillonite concentrations, along with elevated aging temperatures up to 150 °C, regarding rheology and American Petroleum Institute (API) filtration loss. The results indicated that the montmorillonite solution with PEI-GO had lower plastic viscosity (PV) and exhibited the lowest yield point (YP), compared to most inhibitors except potassium chloride (KCl) which signified improved rheological behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation